Evolución de los anuncios publicitarios en la plataforma de youtube - Vivas Garcia, Evelyn Janneth (2023)
YouTube is a platform that is under constant evolution, consequently, the ads that are presented on it, have been changing at the same time. In their early stages they were more primitive and simple, but over time they were admitting advertisements in different formats, even showing audiovisual advertisements. The platform offers various features, such as commenting on videos, subscribing to channels to receive updates, qualifying with "like" or "don't like" videos and sharing content on social networks and other media. In addition, it offers opportunities for creators to earn revenue through monetizing their videos through ads and user subscriptions. Over time, YouTube has added additional features, such as live streams, video game streaming, and the option to rent or buy movies and TV shows. The platform has left a strong influence on digital culture, online education and entertainment, allowing people to share their narratives, skills and interests with a global audience.